2014
DOI: 10.1016/j.dsr2.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of dissolved free amino acids by four cold-water coral species from the Mediterranean Sea

Abstract: Dissolved organic matter, which contains many compounds such as lipids, sugars and amino acids, is an important source of carbon and nitrogen for several symbiotic and asymbiotic tropical coral species. However, there is still no information on its possible uptake by cold-water coral species. In this study, we demonstrated that dissolved organic matter, in the form of dissolved free amino acids (DFAA), is actively absorbed by four cold-water coral species from the Mediterranean Sea. Although the uptake rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…Deep-sea corals are dependent on heterotrophic feeding and therefore generally limited not only in nitrogen, but also in carbon supply (Kiriakoulakis et al, 2004;Roberts et al, 2006). To cover their demands, corals utilize a wide range of food sources including phytodetritus, phytoplankton, zooplankton, dissolved organic matter (Dodds et al, 2007;Gori et al, 2014), and even chemoautotrophic carbon-fixing has been suggested (Middelburg et al, 2015). In line with this, the bacterial microbiome of in situ E. fistula included bacterial taxa with the potential to fix nitrogen and carbon directly (i.e., "dinitrogen-fixing, " "carbon fixation") or indirectly, e.g., from crustacean prey (i.e., "chitin degradation").…”
Section: Putative Functional Differences Between Native Red Sea and Lmentioning
confidence: 99%
“…Deep-sea corals are dependent on heterotrophic feeding and therefore generally limited not only in nitrogen, but also in carbon supply (Kiriakoulakis et al, 2004;Roberts et al, 2006). To cover their demands, corals utilize a wide range of food sources including phytodetritus, phytoplankton, zooplankton, dissolved organic matter (Dodds et al, 2007;Gori et al, 2014), and even chemoautotrophic carbon-fixing has been suggested (Middelburg et al, 2015). In line with this, the bacterial microbiome of in situ E. fistula included bacterial taxa with the potential to fix nitrogen and carbon directly (i.e., "dinitrogen-fixing, " "carbon fixation") or indirectly, e.g., from crustacean prey (i.e., "chitin degradation").…”
Section: Putative Functional Differences Between Native Red Sea and Lmentioning
confidence: 99%
“…Combining observational data and multivariate statistical analyses has provided a wealth of information on ranges of individual environmental parameters tolerated by CWC (e.g., Davies et al, 2008;Davies and Guinotte, 2011). In addition, laboratory experiments provided some insight into maximum and/or minimum tolerated levels of some environmental parameters (e.g., Tsounis et al, 2010;Gori et al, 2014;Movilla et al, 2014;Naumann et al, 2014;Maier et al, 2016;Büscher et al, 2017), however, with partly contrasting results from different studies and areas (e.g., Dodds et al, 2007;Lunden et al, 2014) probably hinting to regional adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent discoveries of hitherto unknown CWC reefs that exist today under rather "extreme" conditions [e.g., in terms of temperature or oxygen (Ramos et al, 2017)], force us to shift the upper and lower thresholds of environmental parameters beyond formerly described values. In addition, laboratory experiments conducted on several common CWC species (e.g., Lophelia pertusa, Madrepora oculata, and Dendrophyllia) provided additional information on their ecological requirements (e.g., in terms of temperature, carbonate system, food supply, and oxygen) (e.g., Tsounis et al, 2010;Gori et al, 2014;Movilla et al, 2014;Naumann et al, 2014;Maier et al, 2016;Büscher et al, 2017) and also indicate region-specific adaptations of CWC to particular environmental parameters (Dodds et al, 2007;Lunden et al, 2014). Furthermore, exceeding/undercutting such environmental thresholds ("tipping point") causing a local extinction of CWC so far has never been documented by field observations.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas DOM needs to be transported to potential consumers (e.g. sponges and coldwater corals; de Goeij et al 2013, Gori et al 2014, Mueller et al 2014 by water movement, which may be advective or turbulent, POM can arrive at the seafloor through gravitational sinking. However, passive organic particle sinking is generally considered insufficient to meet the high metabolic demands of reef communities in the North-Atlantic (Soetaert et al 2016).…”
Section: Introductionmentioning
confidence: 99%